2019
DOI: 10.1002/1878-0261.12579
|View full text |Cite
|
Sign up to set email alerts
|

The transmembrane protein LRIG2 increases tumor progression in skin carcinogenesis

Abstract: Over the last few decades, the number of cases of non‐melanoma skin cancer (NMSC) has risen to over 3 million cases every year worldwide. Members of the ERBB receptor family are important regulators of skin development and homeostasis and, when dysregulated, contribute to skin pathogenesis. In this study, we investigated leucine‐rich repeats and immunoglobulin‐like domains 2 (LRIG2), a transmembrane protein involved in feedback loop regulation of the ERBB receptor family during NMSC. LRIG2 was identified to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…The ERBB4 gene is a member of the ERBB family and plays an important role in the occurrence and development of various tumors [ 28 , 29 ]. Accumulating evidence has shown that ERBB4 plays a critical role in regulating cellular growth, as ERBB4 overexpression promotes proliferation and cellular survival, whereas ERBB4-null cells demonstrate decreased proliferation and cellular survival [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ERBB4 gene is a member of the ERBB family and plays an important role in the occurrence and development of various tumors [ 28 , 29 ]. Accumulating evidence has shown that ERBB4 plays a critical role in regulating cellular growth, as ERBB4 overexpression promotes proliferation and cellular survival, whereas ERBB4-null cells demonstrate decreased proliferation and cellular survival [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…While LRIG1 and LRIG3 are thought to be tumor suppressors, LRIG2 expression is mostly related to poor prognosis [38]. Previously, we have shown that LRIG2 acts as an oncogene in skin cancer affecting ERBB signaling [32]. In this study, we used a LRIG1-TG gain-of-function mouse model to investigate the influence of LRIG1 overexpression on skin tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described [32], total RNA was isolated from all investigated cell lines (HaCaT, A431, A375, SK‐MEL2, SK‐MEL28) using TRIZOL reagent (Invitrogen, Darmstadt, Germany). According to the manufacturer's instructions, 3 µg RNA was reverse‐transcribed in a final volume of 30 µL using RevertAid reverse transcriptase (Thermo Scientific, Schwerte, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of epidermal growth factor receptor (EDFR) leads to activation of metabolic pathways that cause progression of the oral cancer, suggesting that EGFR plays a role in the development of the cancer stem cells [10]. In animal skin cancer model using DMBA, the activity of EGFR pathways are significantly increased compared with control animals [11].…”
Section: Introductionmentioning
confidence: 99%